Effects of sulphuric acid and hot water treatments on seedborne fungi and germination of Stylosanthes hamata, S. guianensis and S. scabra - Nan, Z.B.; Hanson, Jean; Wolde-Mariam, Y. (1998)
Effects of concentrated sulphuric acid and hot water treatments on seedborne fungi and seed germination were studied using a seed lot of Stylosanthes hamata with heavy fungal infection. The effectiveness of the methods developed was further tested on S. guianensis, S. scabra and other lots of S. hamata. The most effective treatments for reducing fungal infection without reducing seed viability were immersion in sulphuric acid for 6 min, immersion in water at 55 degree centigrade for 10 min, and immersion in water at 55 degree centifrade for 5 min + immersion in sulphuric acid for 3 min. The total percentage frequency of infected seeds was reduced from 58.5 percent to 17.3 percent, 12.3 percent and 10.5 percent in S. hamata; from 30.8 percent to 5.5 percent, 4.3 percent and 2.5 percent in S. guianensis; and from 49.3 percent to 13.8 percent, 7.3 percent and 4.3 percent in S. scabra, respectively, by these three treatments. The percentage of hard seeds was reduced from 37 percent to 2 percent in S. guianensis, from 70 percent to 26 percent in S. scabra, and from 44 percent to 17 percent in S. hamata by immersion in water at 55 degree centigrade for 5 min followed by immersion in sulphuric acid for 3 min. Immersion in water at 55 degree centigrade for 10 min also reduced the percentage of hard seed from 37 percent to 6 percent in S. guianensis.